The Hierarchy of the Grounds for Divorce in Transylvanian Reformed Marriage Law in the Second Half of the 19th Century - Nagy, Péter (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
This study aims to analyse the hierarchy of the grounds for divorce in Transylvanian reformed marriage law. It focuses not only on Peter Bod's Marriage Law, but also analyses in detail the practice of marriage courts of Transylvanian Reformed Church. This paper will attempt to determine the reasons and aspects that led to the development of the order of divorce and to present the system of grounds for divorce. It study the practice at the end of the 19th century.